Pembelajaran Paradigma Baru Kurikulum Merdeka Pada Sekolah Dasar - Jusuf , Heni; Sobari, Ahmad (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
The education curriculum continues to change according to technological developments, but the current two-year conditions are different. Since two years ago, in the pandemic era, the curriculum applied in schools is the 2013 curriculum and the prototype curriculum. The prototype curriculum is a development of the 2013 curriculum, also called the emergency curriculum. For the 2022/2023 school year, the government establishes an independent curriculum for schools that are ready to implement it. This technical guidance is very much needed for school principals and teachers so that the implementation of an independent curriculum can be carried out, technical guidance carried out online is able to make participants comfortable, and motivated to keep following until the material is finished, because the technical guidance carried out is arranged very systematically with a well-designed learning design. good. the results of the technical guidance that has been carried out, all participants understand and are ready to implement the independent curriculum and support the implementation of the independent curriculum in their respective schools by making real action reports and sending them to the learning management system.